2019
DOI: 10.1002/adbi.201900103
|View full text |Cite
|
Sign up to set email alerts
|

Computational Analysis of the Mutual Constraints between Single‐Cell Growth and Division Control Models

Abstract: Three models of division control are proposed to achieve cell size homeostasis: sizer, timer, and adder. However, few published studies of division control take into account the dynamics of single‐cell growth and most assume that single‐cell growth is exponential. Here, computational simulations considering exponential, linear, and bilinear growth models are performed. These simulations confirm that a timer division control model alone cannot lead to size homeostasis if the single‐cell growth model is exponent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…We sought to identify which model best described C. elegans growth behavior but were unable to consistently distinguish between linear, exponential, and cubic models using statistical information criterion because of the similarity in the shapes of the growth curves (Figure S6 and Table S2). This result is not surprising because computational simulations have shown that increases in experimental noise, above 2% added noise, limit the correct identification of growth models [35].…”
Section: Resultsmentioning
confidence: 99%
“…We sought to identify which model best described C. elegans growth behavior but were unable to consistently distinguish between linear, exponential, and cubic models using statistical information criterion because of the similarity in the shapes of the growth curves (Figure S6 and Table S2). This result is not surprising because computational simulations have shown that increases in experimental noise, above 2% added noise, limit the correct identification of growth models [35].…”
Section: Resultsmentioning
confidence: 99%
“…However, an important observation very recently established a similar growth kinetics in different species of the acid‐fast bacteria from the genus Mycobacterium (Hannebelle et al, 2020). An elegant theoretical study verified that bilinear growth is able to maintain population‐level size homeostasis (Vuaridel‐Thurre et al, 2020). Whether the cell cycle and its phases can be considered as sizers, adders and/or timers also seems to be elusive and contradictory, and probably different answers might come from different model cells.…”
Section: Discussionmentioning
confidence: 96%
“…During the last couple of years, there have been many, many new results published on both individual cellular growth and population‐level size homeostasis and the connections between these two aspects (Allard et al, 2018; Barber, Amir, & Murray, 2020; Cantwell & Nurse, 2019; Facchetti, Knapp, Chang, & Howard, 2019; Facchetti et al, 2019; Hannebelle et al, 2020; Nordholt, van Heerden, & Bruggeman, 2020; Opalko et al, 2019; Patterson et al, 2019; Pickering et al, 2019; Si et al, 2019; Vuaridel‐Thurre, Vuaridel, Dhar, & McKinney, 2020; Xie & Skotheim, 2020; Zatulovskiy & Skotheim, 2020; Zatulovskiy, Zhang, Berenson, Topacio, & Skotheim, 2020). The model organisms studied vary from unicellular prokaryotes via yeasts to animal cells; moreover, modern techniques have even made possible to examine mammalian cells in tissues in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In general, there are three different models that describe how cells can reach size homeostasis. The sizermechanism controls the beginning of mitosis by a size threshold, for the adder-mechanism the cell size increases by a constant amount independent of initial cell size, and with the timer-mechanism cells grow exponentially for a constant duration (Cadart et al 2018; Vuaridel-Thurre et al 2020). To determine if this correlation applies on the area development of CHO K1 cells, we compared the cell area of single cells at their birth and at their mitosis.…”
Section: Resultsmentioning
confidence: 99%